The leftovers - Perrotta, Tom, 1961- (New York : St. Martin's Press, 2011)
What would happen if The Rapture actually took place and millions of people just disappeared from the earth? How would normal people respond? The residents of Mapleton use a variety of coping mechanisms in this thought-provoking novel about love, connection, and loss.
Keywords: Life change events -- Fiction; Psychological fiction